Distinct health-related risk profiles among middle-aged and older adults with risky alcohol use from the Danish general population. (1st September 2021) - Behrendt, Silke; Kuerbis, Alexis; Becker, Ulrik; Mejldal, Anna; Andersen, Kjeld; Søgaard Nielsen, Anette; Tolstrup, Janne; Holm Eliasen, Marie
Highlights: Middle-aged and older risky drinkers may differ by health-related variables. We conducted an LCA with Danish middle-aged and older risky drinkers. Health indicators included different types of functioning limitations and distress. Up to six distinct health-profiles were found (e.g. class 'pain-related distress'). These risk profiles can inform prevention planning for older risky drinkers. Abstract: Background: Knowledge is lacking on distinct health-related risk profiles among the substantial group of middle-aged and older adults with risky alcohol use (AU). Such profiles could inform the planning of interventions and prevention. Aims: To 1) identify distinct health-related profiles based on different types of health-related functioning limitations and distress and 2) assess associations between these profiles and age, sex, and health-relevant behaviors (e.g., smoking). Methods: Cross-sectional nation-wide Danish health survey with n = 6630 adults aged 55–64 and n = 7605 aged 65–74 with at least risky AU (>84 g ethanol/week in women, >168 in men). Health-related risk profiles were identified with Latent Class Analysis (LCA). Multinomial regression was applied for the association between risk profiles and auxiliary variables. Results: A six-class LCA solution was found among 55–64 year-olds (classes: 'Normative' [61%], 'Distress' [6%], 'Mental health limitations [5%]', 'Pain-related distress [10%]', 'Broad limitations and pain distress [7%]', 'High overall burden' [11%]) and a five-class solution among 65–74 year-olds. Most classes were comparable across age groups. The 'Distress'-class characterized by pain-distress, tiredness-distress, and sleep-related distress (6%) only showed in the younger group. In both age groups, auxiliary covariates (high-risk AU, possible alcohol use disorder, weekly smoking) were positively associated with problematic profile membership (vs. normative class membership). Conclusion: Middle-aged and older adults with risky AU have distinct health-related profiles relevant for the form and content of prevention and interventions. Despite their distinct features, almost all problematic health profiles warrant careful attention regarding high-risk AU and probable alcohol use disorder.